2020
DOI: 10.1128/aem.02299-19
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Eliminating the Detrimental Effect of Thiamine Deficiency on the Oleaginous Yeast Yarrowia lipolytica

Abstract: Thiamine is a vitamin that functions as a cofactor for key enzymes in carbon and energy metabolism in all living cells. While most plants, fungi, and bacteria can synthesize thiamine de novo, the oleaginous yeast Yarrowia lipolytica cannot. In this study, we used proteomics together with physiological characterization to elucidate key metabolic processes influenced and regulated by thiamine availability and to identify the genetic basis of thiamine auxotrophy in Y. lipolytica. Specifically, we found that thiam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 68 publications
0
26
0
Order By: Relevance
“…This modification resulted in an increase in the lipid content by 40% compared with the parental strain when dissolved oxygen (DO) was controlled at 30% of the atmospheric value (Zhang et al, 2019). In a separate study, Walker et al (2020) investigated the effect of thiamine on the physiology of Y. lipolytica and found that thiamine deficiency decreased the protein abundance related to the lipid biosynthesis pathways and energy metabolism. The authors further used the thiamine-regulated promoter P3 to express 4-amino-5-hydroxymethyl-2methylpyrimidine phosphate synthase (THI13) from S. cerevisiae and proved that restoring thiamine synthesis can boost lipid accumulation in Y. lipolytica.…”
Section: Heterologous Gene Expression In Y Lipolyticamentioning
confidence: 99%
“…This modification resulted in an increase in the lipid content by 40% compared with the parental strain when dissolved oxygen (DO) was controlled at 30% of the atmospheric value (Zhang et al, 2019). In a separate study, Walker et al (2020) investigated the effect of thiamine on the physiology of Y. lipolytica and found that thiamine deficiency decreased the protein abundance related to the lipid biosynthesis pathways and energy metabolism. The authors further used the thiamine-regulated promoter P3 to express 4-amino-5-hydroxymethyl-2methylpyrimidine phosphate synthase (THI13) from S. cerevisiae and proved that restoring thiamine synthesis can boost lipid accumulation in Y. lipolytica.…”
Section: Heterologous Gene Expression In Y Lipolyticamentioning
confidence: 99%
“…However, enhanced accumulation of α-KG by disruption of genes directly affecting TCA cycle will undoubtedly cause cellular growth and survival defects circumventing which urges deeper molecular knowledge. In this regard, similar omics data-based findings of the study by Walker et al on the effects of thiamine deficiency on cellular metabolism of thiamine auxotroph Y. lipolytica which was discussed in lipid production improvement strategies, can be helpful (Walker et al, 2020).…”
Section: Nonlipid Productsmentioning
confidence: 67%
“…Released tryptic peptides were then acidified to 0.5% formic acid, filtered through a 10 kDa MWCO spin filter (Vivaspin 2; Sartorius), and quantified by Nanodrop OneC. Three micrograms of peptides were then analyzed by 1D LC-MS/MS using a Vanquish uHPLC coupled directly to an Orbitrap Q Exactive mass spectrometer (Thermo Scientific) as previously described (59). Peptides were separated across a 180 min organic gradient using an in-house pulled nanospray emitter packed with 15 cm of 1.7-micron Kinetex reversed-phase resin (Phenomenex).…”
Section: Methodsmentioning
confidence: 99%